Luminous, pc-scale CO 6-5 emission in the obscured nucleus of NGC 1377 - S. Aalto; S. Muller; F. Costagliola; K. Sakamoto; J. S. Gallagher; N. Falstad; S. König; K. Dasyra; K. Wada; F. Combes; S. García-Burillo; L. E. Kristensen; et al. (EDP SCIENCES S A, 2022)
High-resolution submillimeter line and continuum observations are important in probing the morphology, column density, and dynamics of the molecular gas and dust around obscured active galactic nuclei (AGNs). With high-resolution (0'.06 x 0'.05 (6 x 5 pc)) ALMA 690 GHz observations we have found bright (T-B > 80 K) and compact (full width half maximum size (FWHM) size of 10 x 7 pc) CO 6-5 line emission in the nuclear region of the extremely radio-quiet galaxy NGC 1377. The CO 6-5 intensity is partially aligned with the previously discovered jet/outflow of NGC 1377 and is tracing dense (n > 10(4 )cm(-3)) hot molecular gas at the base of the outflow. The velocity structure is complex and shifts across the jet/outflow are discussed in terms of separate overlapping kinematical components or rotation. High-velocity gas (Delta v +/- 145 km s(-1)) is detected inside r < 2-3 pc and we suggest that it is emerging from an inclined rotating disk or torus of position angle PA = 140 degrees +/- 20 degrees with a dynamical mass of 3 x 10(6 )M(circle dot). This mass is consistent with that of a supermassive black hole (SMBH), as inferred from the M-sigma relation. The gas mass of the proposed disk/torus constitutes <3% of the dynamical mass inside a radius of 3 pc. In contrast to the intense CO 6-5 line emission, we do not detect 690 GHz dust continuum in the nuclear region of NGC 1377. The upper limit of S (690 GHz) less than or similar to 2 mJy implies an H-2 column density N(H-2) < 3 x 10(23) cm(-2) (averaged in the central 6 x 5 pc beam). This is inconsistent with a Compton thick (CT) source and we discuss the possibility that CT obscuration may instead be occurring on smaller subparsec scales or in a larger foreground structure. From SED fitting we suggest that half of the IR emission of NGC 1377 is nuclear and the rest, mostly the far-infrared (FIR), is emerging from larger scales. The extreme radio quietness, and the lack of emission from other star formation tracers, raise questions on the origin of the FIR emission. We discuss the possibility that it arises from AGN-heated dust along the minor axis.